Optimasi Formula Gel Fraksi Teraktif Buah Mengkudu (Morinda citrifolia L.) Sebagai Antioksidan Topikal - Erlinda Novita Sari; Ika Purwidyaningrum; Iswandi Iswandi (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Flavonoid compounds and vitamin C from noni fruit have the potential to be antioxidants. The unpleasant odor, soft texture, and unpleasant taste of noni fruit are minimized through a fractionation process and formulated into a gel preparation, which is expected to increase the acceptance of noni fruit in the community. Objective: to determine the optimal gel formula of the most active fraction of noni fruit with variations of HPMC, carbopol 940, and propylene glycol through critical parameters of viscosity, pH, and antioxidant activity using the Simplex Lattice Design method. Method: The extraction used is maceration and continued with a fractionation process. Physical properties tests include organoleptic, homogeneity, viscosity, adhesiveness, spreadability, and pH. Determination of the IC50 value of antioxidants with DPPH using a UV-Vis spectrophotometer. The statistical results of the data obtained were processed using ANOVA, Wilcoxon, and the T-test. Results: showed that the noni fruit fraction that had the best antioxidant activity was the ethyl acetate fraction (20.35±0.18 ppm), variations of 13 gel formula compositions with the most optimal viscosity, pH, and IC50 responses were carbopol 940:HPMC 8060-M: propylene glycol (1.491:0.509:8.000). Variations in the combination of HPMC 8060-M, carbopol 940, and propylene glycol in the gel preparation of the most active noni fruit fraction affected the critical parameters of viscosity, pH, and antioxidant activity. Conclusion: The ethyl acetate fraction has the best antioxidant activity and the optimal gel formula composition is carbopol 940:HPMC 8060-M:propylene glycol (1.491:0.509:8.000) which is predicted to have a very high desirability value (0.917) and has been validated.